A survey that contributes to the development of a framework to evaluate health and safety strategies in supply chains. (1st January 2012) - Lehaney, Brian; Diugwu, Ikechukwu A.; Willemyns, Michael; Hosie, Peter
This paper reports on the results of survey that was part of wider research to link small to medium enterprises (SMEs) and larger organisations to help improve the health and safety records of SMEs. The survey results suggest that networking, as virtual organisations, would be a valuable way to link SMEs with their larger counterparts, partly because SMEs do not have the resources and time to release members of staff easily to attend physical workshops and other events. SMEs are important to many economies, but tend to have poor health and safety records. It is in the interests of larger organisations to assist SMEs within their supply chains, as the effects of absences resulting from poor health and safety management in SMEs result in supplies being disrupted. The research focussed on the construction industry. It is mapped to existing literature in relevant domains.